THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN COMPUTER SCIENCE - Mirzatullayeva Sayyora (Ustozlar uchun, 2025)
Abstract:Artificial Intelligence (AI) has emerged as one of the most transformative forces in modern computer science. This paper investigates the core role of AI in reshaping computational methods, automating tasks, enhancing decision-making, and facilitating breakthroughs in subfields such as machine learning, robotics, and data analytics. The study further discusses ethical concerns, algorithmic bias, and the future trajectory of AI technologies in the digital age.